QT dispersion in carbon monoxide poisoning - Atescelik, M.; Bozdemir, M. N.; Yildiz, M.; Gurbuz, S.; Ayranci, M.; Goktekin, M. C.; Eken, C. (Verduci Publisher, 2012)
Background: Carbon monoxide (CO) poisoning are serious health problems, and effect of reducing the blood's oxygen carrying capacity. Deaths due to CO poisoning are mostly related to myocardial injury and central nervous system pathologies. Aim: The objective of this study was to determine the relationship between carbon monoxide intoxication, QT dispersion, and cardiac markers. Materials and Methods: Patients with possible CO intoxication symptoms were evaluated to be eligible for the study. Patients' demographic data, carboxyhemoglobin levels, cardiac markers and QT interval measurements were recorded to the study form. Results: A total of 127 patients (79 CO intoxicated and 48 controls) were included into the study with a mean age of 38.6 +/- 14.1 years and 62.2% of them were female. Average levels of patient's carboxyhemoglobin were 21.3 +/- 9. OT dispersion (39.0 +/- 10.8 vs 24.4 +/- 6.2; p < 0,001) and corrected QT dispersion (46.2 +/- 14.7 vs 25.3 +/- 6.2; p < 0.001) were longer than the control group. Both QT dispersion (39.0 I 10.8 vs 23.6 +/- 7.0; p < 0.001) or corrected QT dispersion (46.2 +/- 14.7 vs 27.1 +/- 8.7; p < 0.001) were also decreased after one week later from the admission. Conclusion: Carbon monoxide intoxication is related to increased OT dispersion. Emergency physicians should measure QT dispersion in CO intoxicated patients in order to predict the electrical instability in myocardium and future adverse events.
Keywords: Carbon monoxide poisoning; QT dispersion; Cardiac marker; Emergency Department